2021
DOI: 10.1038/s41598-021-85206-5
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasound-irradiated synthesis of 3-mercaptopropyl trimethoxysilane-modified hydroxyapatite derived from fish-scale residues followed by ultrasound-assisted organic dyes removal

Abstract: We report a novel method for the synthesis of 3-mercaptopropyl trimethoxysilane-modified hydroxyapatite (FHAP-SH) derived from fish-scale residues by using ultrasound irradiation. Scanning electron microscopy, transmission electron microscopy, energy-dispersive spectroscopy, X-ray diffraction, and Fourier transform infrared spectroscopy were used for the FHAP-SH characterization. Then, the organic dye adsorption on the FHAP-SH was monitored through an ultrasound process. After the dye removal optimization, sig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 39 publications
1
7
0
Order By: Relevance
“…This is in line with the findings of Khoo et al [65], who analyzed the production and extraction of HAp in a calcination process at 700 • C and concluded that these parameters are optimal for the extraction of HAp, allowing for the organic content to be removed and a highly crystalline structure to be formed [65]. Many studies have demonstrated the effectiveness of the synthesis of HAp from marine waste such as scales, bones, shells, and skins [66,67]. These studies applied ultrasound technologies to obtain a highly adsorbent HAp enriched with another chemical compound (3-mercaptopropyl trimethoxysilanes) [66].…”
Section: Hydroxyapatite (Hap)supporting
confidence: 84%
“…This is in line with the findings of Khoo et al [65], who analyzed the production and extraction of HAp in a calcination process at 700 • C and concluded that these parameters are optimal for the extraction of HAp, allowing for the organic content to be removed and a highly crystalline structure to be formed [65]. Many studies have demonstrated the effectiveness of the synthesis of HAp from marine waste such as scales, bones, shells, and skins [66,67]. These studies applied ultrasound technologies to obtain a highly adsorbent HAp enriched with another chemical compound (3-mercaptopropyl trimethoxysilanes) [66].…”
Section: Hydroxyapatite (Hap)supporting
confidence: 84%
“…(2019) revealed the presence of a large amount of hydroxyl group in HAp derived from fish contributing to a significant increase of the active adsorbing sites for the heavy metals like lead, arsenic, copper, cadmium, and mercury with adsorption capability of 162.4 mg/g for copper and 128.7 mg/g for cadmium. Sricharoen et al . (2021) also reported a high adsorption capability of HAp derived from fish of up to 227.2 mg/g.…”
Section: Discussionmentioning
confidence: 99%
“…The pristine PU sponge was immersed in the GO aqueous solution and then dried at high temperature to obtain a GO-coated sponge (GO-PU). To address the hydrophilicity of the GO-PU [36], silanization modification with DTMS was conducted to introduce low-energy materials on the surface of the GO-PU [37,38]. Then DTMS-GO-PU was treated by a thermal curing reduction process at a high temperature in an argon-hydrogen atmosphere to obtain a superhydrophobic and superlipophilic DTMS-rGO-PU sponge.…”
Section: Determination Of Optimal Preparation Conditions Of Dtms-rgo-...mentioning
confidence: 99%